Inhibition of Thrombosis by a Selective Fibrinogen Receptor Antagonist without Effect on Bleeding Time - Tschopp, Juerg F; Mazur, Curt; Gould, Kenneth; Connolly, Raymond; Pierschbacher, Michael D (Thrombosis and Haemostasis, 1994)
Membrane glycoprotein αIIbβ3 on platelets plays a pivotal role in hemostasis by mediating RGD-(arginine-glycine-aspartic acid)-dependent platelet adhesion and aggregation. Antagonists of αIIbβ3 ligand binding function, such as antibodies, snake venom peptides, or synthetic RGD-containing peptides can completely inhibit platelet aggregation in vitro and cause significant prolongation of bleeding times when injected into experimental animals. The in vitro and in vivo properties of an αIIbβ3 specific RGD-containing peptide 2G (G(Ten)GHRGDLRCA) were compared to two non-specific RGD-containing peptides IN (G(Pen)GRGDTPCA) and 2H (GRGDSPDG). All three peptides have similar IC50 values in human patelet aggregation (14-22 μM) and ELISA-based μIIbβ3 receptor assays (0.2–0.3 αM) but show different inhibitory activity (IC50 values) in the αv㯂5 (2G = 10 μM; IN = 0.06 μM; 2H = 0.05 μM) and receptor assays (2G = 8.3 μM; IN = 0.06 μM; 2H = 0.04). The αIIbβ3 specific peptide 2G had no effect on monolayers of human saphenous vein endothelial cells while IN and 2H caused many cells to detach and contract. Peptides 2G and IN inhibited ADP-stimulated ex vivo platelet aggregation in dogs in a dose dependent manner. When complete inhibition (>90%) of ex vivo platelet aggregation was achieved with either a 10 mg/kg bolus followed by a 16mg/kg/h infusion of 2G or with a 15 mg/kg bolus and 24 mg/kg/h infusion of IN, peptide IN caused a dose-dependent increase of the template bleeding time, while peptide 2G had no effect, even at doses up to 15 mg/kg bolus followed by 24 mg/kg/h infusion. The in vivo properties of peptides 2G and 2H were also examined in a baboon ex vivo shunt model for their ability to block platelet uptake and fibrinogen deposition on small caliber GORE-TEX® grafts and for their effect on the hemostatic system. Systemic administration of peptide 2G at 10 mg/kg bolus followed by 10 mg/kg/h infusion (or at a 2-fold lower dose) abolished platelet uptake and fibrinogen deposition on the graft surface without affecting the hemostasis and template bleeding time of the animal. By contrast, peptide 2H caused a 3-4-fold increase in bleeding time at a dose of 10 mg/kg. The results suggest that efficacy and the effect of specific aIIbp3antagonists on bleeding time can be separated and that selective aIIbP3 receptor blockade may be an efficient and safe approach to improve the patency and the success rate pf small caliber vascular grafts and to treat unwanted platelet-dependent thromboses. While peptide 2G may represent a unique class of antithrombotic agent, the clinical use of this type of molecule would require a significant enhancement in potency.